Respirable Silica Dust Exposure of Migrant Workers Informing Regulatory Intervention in Engineered Stone Fabrication - Mahinda Seneviratne; Kiran Shankar; Phillip Cantrell; Aklesh Nand (Elsevier, 2024)
Background: Silicosis among workers who fabricate engineered stone products in micro or small-sized enterprises (MSEs) was reported from several countries. Workplace exposure data of these workers at high risk of exposure to respirable crystalline silica (RCS) dust are limited. Methods: We surveyed workers performing cutting, shaping and polishing tasks at 6 engineered stone fabricating MSEs in Sydney, Australia prior to regulatory intervention. Personal exposure to airborne RCS dust in 34 workers was measured, work practices were observed using a checklist and worker demography recorded. Results: Personal respirable dust measurements showed exposures above the Australian workplace exposure standard (WES) of 0.1 mg/m3 TWA-8 hours for RCS in 85% of workers who performed dry tasks and amongst 71% using water-fed tools. Dust exposure controls were inadequate with ineffective ventilation and inappropriate respiratory protection. All 34 workers sampled were identified as overseas-born migrants, mostly from three linguistic groups. Conclusions: Workplace exposure data from this survey showed that workers in engineered stone fabricating MSEs were exposed to RCS dust levels which may be associated with a high risk of developing silicosis. The survey findings were useful to inform a comprehensive regulatory intervention program involving diverse hazard communication tools and enforcing improved exposure controls. We conclude that modest occupational hygiene surveys in MSEs, with attention to workers' demographic factors can influence the effectiveness of intervention programs. Occupational health practitioners should address these potential determinants of hazardous exposures in their workplace surveys to prevent illness such as silicosis in vulnerable workers.